The urgency of Mandatory Provision of Covid-19 Vaccination Public Services - Juwita Rizkiyawati Abdullah (Estudiante Law Journal, 2022)
The purpose of this study is to find out and analyze the covid-19 vaccination against the provision of public services in Talaga Jaya District and the urgency of providing covid-19 vaccination requirements for the provision of public services by the Talaga Jaya District government This type of research is qualitative field research and uses random sampling. The population in the study is the people who have carried out the covid-19 vaccination. Data collection was carried out with interviews, literature studies, and documentation. The results showed that in the process of implementing the COVID-19 vaccination, there were problems. Therefore, to reach the implementation of the COVID-19 vaccination evenly, the sub-district government and village government carry out mass and door-to-door vaccinations. In the implementation of the covid-19 vaccination, it has been regulated in presidential regulation number 14 of 2021 where people who refuse the vaccine will be subject to sanctions. The policy raises polemics because vaccinations are supposed to be voluntary because they relate to the individual freedom of citizens